93-(7x+6)=7(x+6)+x

Simple and best practice solution for 93-(7x+6)=7(x+6)+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 93-(7x+6)=7(x+6)+x equation:


Simplifying
93 + -1(7x + 6) = 7(x + 6) + x

Reorder the terms:
93 + -1(6 + 7x) = 7(x + 6) + x
93 + (6 * -1 + 7x * -1) = 7(x + 6) + x
93 + (-6 + -7x) = 7(x + 6) + x

Combine like terms: 93 + -6 = 87
87 + -7x = 7(x + 6) + x

Reorder the terms:
87 + -7x = 7(6 + x) + x
87 + -7x = (6 * 7 + x * 7) + x
87 + -7x = (42 + 7x) + x

Combine like terms: 7x + x = 8x
87 + -7x = 42 + 8x

Solving
87 + -7x = 42 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
87 + -7x + -8x = 42 + 8x + -8x

Combine like terms: -7x + -8x = -15x
87 + -15x = 42 + 8x + -8x

Combine like terms: 8x + -8x = 0
87 + -15x = 42 + 0
87 + -15x = 42

Add '-87' to each side of the equation.
87 + -87 + -15x = 42 + -87

Combine like terms: 87 + -87 = 0
0 + -15x = 42 + -87
-15x = 42 + -87

Combine like terms: 42 + -87 = -45
-15x = -45

Divide each side by '-15'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x^2+14x+59=0 | | Ab+c=2 | | 0=p-20/-2 | | 8x+9y-(2x+y)= | | log(x)+8.75=0 | | -2(6x-7)+6x=5+2(2x-3) | | j+16=-10-j | | 20sinx=10 | | 10x+9-9x-15= | | 4n-40=7(-2nt+2) | | 4/100= | | 4/109= | | 7/8=-2/3x-5 | | (2x-3)+(x+7)=42 | | -2=d-17/-1 | | 2x+3=112 | | 5a-3a=45-9 | | 25x-60=115 | | q^2+2g=323 | | 3x-20=1x | | 4v+8=26-2y | | 10x^3+11x^2-6x-2=0 | | 16(7c-1)-14=110c+16 | | 15.2=x+y | | 4t-3.5=12.5 | | x-20=1/2x-4 | | 52=xy | | -18+11z=18+13z | | 3.8x+8.93=-17.29 | | -(2-3(2.2))+2.2=9-2.2 | | 4(w+5)=-2(5w-8)+6w | | 12m=12+11m |

Equations solver categories